Mycobacterium tuberculosis Heat-Shock Protein 16.3 Induces Macrophage M2 Polarization Through CCRL2/CX3CR1 - Zhang, Yanhao (Inflammation, 2019)
Mycobacterium tuberculosis, the pathogen of tuberculosis (TB), can survive in host macrophages and induce macrophages to M2 phenotype might result in latent MTB infection. During the latent phase, the expression of MTB heat-shock protein 16.3 (Hsp16.3) is markedly increased among most of bacterial proteins, but the role of Hsp16.3 in macrophage M2 polarization is not clear. In this work, we found that macrophages incubated with 100 ng/ml MTB Hsp16.3 increased the production of Arg-1, IL-10, TGF-beta, and CD206. These results showed that MTB Hsp16.3 may induce macrophage M2 phenotype. And the interaction of Hsp16.3 with macrophages was found to depend on chemokine receptors CCRL2 and CX3CR1. Additionally, we used overexpression and silencing techniques to further verify the effect of CCRL2 and CX3CR1 on MTB Hsp16.3-induced M2 polarization macrophages. Furthermore, we explored the downstream signaling molecules of CCRL2 and CX3CR1 and we found MTB Hsp16.3 altered the signal transduction of the AKT/ERK/p38-MAPK. Taken together, this study provides evidence that MTB Hsp16.3 promotes macrophages to M2 phenotype and explores its underlying mechanism.